Optimization of the National Unity and Political Agency of Malang City in an Effort to Empower Community Organizations in Malang City - Aditya Putra Pramana; Asep Nurjaman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In accordance with the 2013 Law on Community Organizations (Article 40) it is emphasized that the Government and Local Governments are required to empower Community Organizations to improve performance and maintain the survival of Community Organizations. The main focus of this research is to find out how to optimize the National Unity and Political Agency of Malang City in an effort to empower Community Organizations in Malang City, and what are the obstacles in its implementation. In this study using qualitative research methods with a descriptive approach. Based on the research that has been carried out, through the National Unity and Political Agency of Malang City, it is in line with the objectives of the Regional Regulation related to the empowerment of Community Organizations, namely maintaining the survival of Community Organizations, improving the performance of Community Organizations, strengthening the institutional capacity of Community Organizations, and improving the quality of human resources of Community Organizations. In optimizing the empowerment of Community Organizations carried out by the National Unity and Political Agency of Malang city, the target to be achieved in increasing the capacity of Community Organizations is to improve the quality of human resources (HR) of Community Organizations, Then strengthen capacity in improving the performance of Community Organizations. As well as increasing the capacity of Community Organizations in maintaining the survival of Community Organizations through their existence.